Current Studies in Social Sciences VIII (Spring) - İşler, İlknur and Kaptaner, Harun and Yalçın, Melike and Şahan, Ferit Çağdaş and Demirbay, Sevim Gülin and Gündüz, Fatma Feyza (Academician Publishing Book DOI Portal, 2024)
-